Quality of the analysis—A performance management system for the analytical stage of child‐protection investigations. Issue 4 (1st June 2020) - Karlsson, Henrik; Avby, Gunilla; Svendsen, Tore
Abstract: This article presents a performance management system for reviewing the quality of written analyses in child‐protection investigations. The system, called quality of the analysis (QUAL), is based on the Swedish adaptation of the British Integrated Children's System and Framework for the Assessment of Children in Need and their Families called Children's Needs in Focus (BBIC). QUAL was applied to 280 child‐protection investigations to review the compliance with the BBIC standards. The investigations took place in 2011 and 2014. The results indicate improvements in various quality indicators, such as answers provided to all investigative questions, both risk and protective factors documented, and an assessment of the child's need for protection or support documented. However, in 40% of the investigations from 2014, the analytical stage was more a summary than an analysis. Many countries struggle to find and develop tools that can provide feasible systematic feedback on professional performance and support quality improvement in child‐protection work. We suggest that QUAL can be used as one method among others to develop and strengthen the analytical work in practice by visualizing and monitoring the written analysis. QUAL may function as a tool to stimulate professional development, facilitate organizational learning, and improve investigative work.